2020
DOI: 10.21307/asam-2019-002
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Anaesthesia During Space Exploration Missions

Abstract: Aim NASA and private spacefaring companies plan to send exploration missions to mars within the next two decades. The environment of space, duration of the mission, distance from earth, and limited available resources present significant challenges for the provision of health care. It has been estimated that at least one medical emergency is likely to occur during such a mission, which may necessitate surgical treatment, and therefore anaesthesia. The provision of safe anaesthesia faces challenges arising from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Facing these challenges, some scientists conducted clinical trials in a simulated environment, they compared the use of video-laryngoscopy in microgravity between the naïve and expertise in airway management. Results suggested that video-laryngoscopy help health care-givers to overcome these factors and it also decreases the difference in intubation efficacy between naive and expertise [21].…”
Section: Challenges In Airway Management During Space Exploration Missionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Facing these challenges, some scientists conducted clinical trials in a simulated environment, they compared the use of video-laryngoscopy in microgravity between the naïve and expertise in airway management. Results suggested that video-laryngoscopy help health care-givers to overcome these factors and it also decreases the difference in intubation efficacy between naive and expertise [21].…”
Section: Challenges In Airway Management During Space Exploration Missionsmentioning
confidence: 99%
“…Physiological accommodation to microgravity may hinder any planning of anesthesia. A previously published assumption for anesthesia airway management reported monitoring, preoxygenation, induction then bag -mask ventilation then they used Rocuronium as a muscle relaxant, followed by endotracheal tube insertion using video laryngoscopy, the tube size was smaller than the proper size to avoid edema [21].…”
Section: Anesthesia and Airway Management In Microgravitymentioning
confidence: 99%